OP0233 Do Clinical Symptoms in the Girdles of Polymyalgia Rheumatica Patients Correlate with Intensity of FDG Uptake?. (10th June 2014) - Camellino, D.; Paparo, F.; Zampogna, G.; Morbelli, S.; Cutolo, M.; Sambuceti, G.; Cimmino, M.A.
Abstract : Background: Polymyalgia rheumatica (PMR) is an inflammatory disease of the elderly characterized by girdle pain and systemic symptoms. Imaging techniques, such as 18F-fluorodesoxyglucose (FDG)-PET/CT, have demonstrated that inflammation is localized mainly in the joint capsule and in bursae, with occasional large vessel vasculitis. However, the correspondence between FDG uptake and subjective symptoms is unclear. We have recently demonstrated that interspinous bursitis is typical of PMR, although it does not associate with pain. Objectives: To test if FDG uptake, which is frequently seen in the girdles of PMR patients, is associated with the clinical experience of pain in the individual patients. Methods: Eighty-four patients affected by PMR according to the ACR/EULAR criteria were studied. A standardized clinical examination, including pain at pressure of the long head of the biceps (LHB), the subacromial area (SA), the ischiatic (IB) and trochanteric (TB) bursae, and at mobilization of the shoulder and hip girdles, was performed immediately before PET/CT. After a minimum of six hours fasting, a dose of 4.8-5.2 MBq of FDG per kilogram body weight was injected through a peripheral vein catheter. Data acquisition started between 60 and 90 minutes after tracer administration. Patients underwent simultaneous FDG-PET and CT imaging from the skull base to the knee using an integrated PET/CT scanner (Hirez; Siemens Medical Solutions, Knoxville TN, USA). PET raw data were reconstructed by means of ordered subset expectation maximization and attenuation correction was performed using the CT raw data. The entire CT dataset was fused with the 3-dimensional PET images using an integrated software interface (Syngo Image Fusion; Siemens Erlangen, Germany) to create superimposed anatomical images. Joint uptake was scored relative to liver uptake as 0=no uptake present, 1=lower than liver uptake, 2=similar to liver uptake, 3=higher than liver uptake. Results: A history of shoulder pain was present in all patients, whereas that of the pelvic girdle was present in 42/84 (50%). The concordance between pain elicited in the different areas and FDG uptake is shown in the table for the right (R) and left (L) sides. At clinical examination, 11/84 (13.1%) patients reported spontaneous pain or pain on passive motion which was clearly more intense in one shoulder. In these cases, tracer uptake was more intense in the symptomatic side in only 2, whereas in the remaining ones it was symmetrically distributed (bilaterally absent in 1 and bilaterally present in 8). Pelvic pain side was discordant in only 1 patient. The TB and IB were involved more often at PET than clinically. Conclusions: The concordance between pain and FDG uptake in the girdles of PMR patients is only modest, except for shoulder capsulitis/synovitis, suggesting that factors other than inflammation visible at PET could contribute to clinical presentation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3011